PROLOG. Patient management in the office - American College of Obstetricians and Gynecologists (2022)
"PROLOG: Patient Management in Office is the premier learning tool for staying up to date in the specialty area. Consisting of an assessment book and critique book, PROLOG is an effective, self-directed study resource and reference for both obstetricians-gynecologists and those in training. The content is peer-reviewed, current, and clinically relevant. Upon completion, users of this unit should be able to: Identify epidemiologic factors that contribute to women's health issues encountered in office practice Determine appropriate screening approaches to identify health conditions in women Correlate presenting signs and symptoms with appropriate diagnostic tools Describe appropriate traditional and alternative management strategies for select conditions encountered in office practice Counsel patients about the impact of health and illness throughout their lives and about risks and benefits of treatment Apply professional medical ethics to the practice of obstetrics and gynecology Incorporate appropriate legal, risk management, and office management guidelines and techniques in clinical practice"--
[v. 1]. Critique book
"Personal Review of Learning in Obstetrics and Gynecology".
Includes bibliographical references and index.
Keywords: Genital Diseases, Female; Pregnancy; Pregnancy Complications; Primary Health Care; Women's Health; Examination Questions